2014
DOI: 10.7763/ijcea.2014.v5.387
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pb(II) on Nano Sized SnO2 Derived from Sol-Gel Method

Abstract: Abstract-This study investigates the applicability of SnO 2 nanoparticles for the removal of Pb(II) from waste water . SnO 2 nano particles of 15 nm size were synthesized using a solgel method and characterized by X-ray diffraction (XRD), FTIR, SEM and transmission electron microscope (TEM). Batch experiments were carried out to study the adsorption kinetics of Pb(II) on SnO 2 . The effect of varying parameters such as contact time and P H on the adsorption process were examined. The adsorption process was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
4
1
Order By: Relevance
“…For the SnO 2 sample synthesized via the modified polyacrylamide gel route, in a recent published study [25] reported a calculated crystallite size of the sample prepared by using oxalic acid as the chelating agent at 118 nm. Another study on the synthesis of the nanoparticles tin oxide (SnO 2 ) using citric acid as the chelating agent at 15 nm [26]. Therefore, our values are much lower than the reported data.…”
Section: Xrd Analysiscontrasting
confidence: 72%
“…For the SnO 2 sample synthesized via the modified polyacrylamide gel route, in a recent published study [25] reported a calculated crystallite size of the sample prepared by using oxalic acid as the chelating agent at 118 nm. Another study on the synthesis of the nanoparticles tin oxide (SnO 2 ) using citric acid as the chelating agent at 15 nm [26]. Therefore, our values are much lower than the reported data.…”
Section: Xrd Analysiscontrasting
confidence: 72%
“…Figure 1 represents the absorbance of PVP/PEO/SiC and PVP/PEO/TiO 2 films with wavelength. The PVP/PEO/SiC and PVP/PEO/TiO 2 nanocomposites samples have high values of absorbance for the UV radiation with attributed to the electrons excitation at UV light [9]. The absorption values of (PVP-PEO) blend rise with rising in SiC and TiO 2 nanoparticles' ratios, which may be related to the absorption and scattering the photons by the charge carriers of SiC and TiO 2 nanoparticles as shown in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…43,45 These oxygen vacancy defects act as dipoles and enhance the dielectric properties of the material. 46 The emission of green coloured light around 519 nm has been assigned to the presence of Zn and oxygen at interstitial positions. [47][48][49] To check the effect of depositing ZnO nanoparticles on electrodes, the capacitance without and with ZnO deposition has been computed.…”
Section: Resultsmentioning
confidence: 99%
“… 43,45 These oxygen vacancy defects act as dipoles and enhance the dielectric properties of the material. 46 The emission of green coloured light around 519 nm has been assigned to the presence of Zn and oxygen at interstitial positions. 47–49 …”
Section: Resultsmentioning
confidence: 99%